Evaluation in Physical Education: an analysis in state and municipal schools in Maringá-PR - Saray Giovana dos Santos; Gislaine Gonçalves (Revista da Educação Física, 2008)
Problems related to evaluation deal with many issues that Physical Education, as a pedagogical subject, has been facing. In order to investigate these aspects, this study has as its aim to analyse how and with purpose, the professionals from the area of Physical Education are evaluating studentes from the 5th to the 8th forms in state and municipal schools in Maringá. A questionnaire was used. The sample was formed by 30 teachers from 12 schools: 15 teachers from state schools and 15 from municipal schools. Descriptive statistics at simple frequency level and non-parametric test (χ2) were used. Results show that evaluation in the subject Physical Education is performed only to follow the norms, without planning and consequently without pre-defined educational objectives showing, thus, the contradictions and confusions inherent to evaluation modalities by the professionals of this area. These professionals demonstrated the precaroiusness of the understanding of evaluation role in teaching-learning process.